EVALUATION OF A MATHEMATICAL MODEL APPLIED TO THE SEPARATION BY IONIC MONOVALENT ELUTION CHROMATOGRAPHIC - Arbildo López, A. (1998)
In the present work is evaluated an applicable mathematical model to the separations by ion-exchange chromatography of ions monovalents in aqueous solutions, being determined the parameters of the model as of gathered experimental data of the bibliography and data simulated with mean zero and standard deviation of 0.05. It has been found that for ions monovalents such as sodium, potassium, chloride, iodur and bromide the percent variations of the parameters are < ±5%, < ±35% and < ±147% for the reduced speed of the fluid, the coefficient of reduced axial dispersion and that of deviation with respect to a linear isothermal respectively; they with 97.5 percent certainty.